Algebraic errors in university thresholds. (UNIHumanitas, 2013)
When talking to university level mathematics teachers, it is common for them to express a certain dissatisfaction regarding the prior knowledge that students arrive with and their performance in mathematics subjects, in which generally, the performance is low, which produces a delay in their professional training and phenomena manifested year after year such as: Low scores in university entrance exams. Marked heterogeneity between students from different educational centers, High failure rates in mathematics evaluations both in the CPA and in the career courses. In addition to low performance, the same teachers detect errors in the mathematical productions of students even at the university level, which translates into incorrect answers and an inadequate understanding of the contents that produce deficiencies when advancing in the construction of the mathematical knowledge of the students and therefore hinder their progress in their university career. Based on this situation, raised by mathematics teachers from the National University of Itapúa, this research sought to analyze these errors from the difficulties that produce them, understanding difficulties as the procedures poorly performed in the exercise that lead to an incorrect resolution of the same. In the first phase of the analysis, the difficulties in Algebra that students present when solving the items of a diagnostic test applied in the first week of the Admission Test Course of the Faculty of Engineering of the National University of Itapúa were identified, and based on these, to present a categorization of errors committed based on the difficulties that produce them; taking into account that Algebra is within the mandatory curricular space granted to mathematics at the secondary level of the National educational system; and considering that the diagnostic test applied to these students is an important source of information on the mathematical training received in the previous years of formal education. The reason why the Faculty of Engineering has been selected for the study is that, due to the type of courses offered at this faculty, there is a greater requirement for adequate mathematical training in students and assuming that, since this is known to the applicants, students who have a positive attitude towards this area of ​​knowledge enroll in this course, thus avoiding the affective component influencing the results.
Keywords: Algebraic errors; university